2022
DOI: 10.3389/fnagi.2022.1011510
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of cognitive reserve on cognitive function in patients with Acute Ischemic Stroke

Abstract: BackgroundRecovery of cognitive function after stroke has inter-individual variability. The theory of cognitive reserve offers a potential explanation of the variability in cognitive function after stroke.ObjectiveThis study aimed to investigate the moderating effect of cognitive reserve on the relationship between the stroke severity and cognitive function after stroke.Materials and methodsA total of 220 patients with Acute Ischemic Stroke (AIS) were recruited in 2021 from two stroke centers in Nanjing, China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In this case, when neuronal damage occurs, there are recruitment and activation of other brain networks to carry out these functions [ 41 ]. This ability to compensate for the damage caused is determined by experiences and static factors such as intelligence level, work achievements, or educational level [ 42 , 43 , 44 ]. Our results might be explained because most of the scientific literature has evaluated the relationship between these variables after evaluating the efficacy of rehabilitation programs in stroke participants.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, when neuronal damage occurs, there are recruitment and activation of other brain networks to carry out these functions [ 41 ]. This ability to compensate for the damage caused is determined by experiences and static factors such as intelligence level, work achievements, or educational level [ 42 , 43 , 44 ]. Our results might be explained because most of the scientific literature has evaluated the relationship between these variables after evaluating the efficacy of rehabilitation programs in stroke participants.…”
Section: Discussionmentioning
confidence: 99%
“…These studies found that after a certain level of educational attainment, additional schooling does not contribute to further reductions in risk of cognitive impairment. 20,21 However, a recent systematic review 22 and 2 stroke studies 23,24 which examined the association of cognitive reserve and poststroke cognitive function did not report such an effect; further investigation is therefore warranted. The idea that cognitive reserve, operationalized as level of education, could delay the expression of the clinical manifestation of brain pathology has been discussed in the context of Alzheimer disease and could be extended to patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…It also found that a higher level of education or occupation was associated with a faster recovery. Additionally, a recent study done in 2022 showed that patients with a higher level of CR had better cognitive function after experiencing an acute ischemic stroke ( Li et al, 2022 ). These findings suggest a protective effect with higher CR.…”
Section: Cognitive Reservementioning
confidence: 99%